Etika Komunikasi di Media Sosial Tiktok Untuk Mengantisipasi Fenomena Bullying - Rambe, Nur Ummudiyah; Khoiri, Nispul; Qarai, Waizul (Jurnal Manajemen Akuntansi (JUMSI), 2024)
The aim of this study is to analyze and understand the practices of communication ethics that can be implemented in the usage of the TikTok social media platform in order to anticipate the bullying phenomenon. TikTok social media has become one of the popular platforms for its users to share short video content. However, the increasing number of TikTok users also has the potential to amplify the risk of the bullying phenomenon on this platform. This research utilizes a qualitative approach with a content analysis method. Data is collected from videos and comments related to TikTok usage as well as communication practices within it. The analysis is conducted with a focus on identifying patterns of bullying behavior, as well as users' efforts to apply communication ethics to reduce the risk of bullying. The results of this research provide insights into various forms of bullying that emerge on TikTok and how communication ethics can be implemented by users as preventive measures. The implications of this research involve the formulation of guidelines for ethical communication practices that can be disseminated to TikTok users, policymakers, and other stakeholders in order to create a safer and more dignified environment on the platform.